Efektivitas Penanganan Speech Delay Anak Usia Dini pada Siswa PAUD Kota Samarinda - Handayani, Yurni; Wardana, Kautsar Eka (UIN Sultan Aji Muhammad Idris Samarinda, 2023)
Speech delay in early childhood is a matter of concern for all parents, especially schools that accept children with these conditions. This is because the delay in speech is very important to note because one of the ways children can interact with their surroundings or peers is through communication. This research was conducted to see the effectiveness of handling speech delay children in early childhood at PAUD in Samarinda City. This type of research uses qualitative research. The instruments of qualitative research are humans or research themselves by listening, observing, asking, and taking research data in the field. Data was obtained through observation, interviews, and documentation. The results of research on speech delay or speech delay in early childhood are due to heredity, gender, excessive giving of gifts, a lack of parental affection and supervision in child care, and the absence of support from parents, family, and the environment. So, those children become children with speech delays, commonly referred to as speech delays.